2016
DOI: 10.1149/2.0731605jes
|View full text |Cite
|
Sign up to set email alerts
|

Film Properties of Electropolymerized Polypyrrole for a Sulfur/Ketjenblack Cathode in Lithium Secondary Batteries

Abstract: A novel polypyrrole (PPy) film was investigated to determine the optimal conditions for operation in a Li/S battery. The PPy film was prepared by oxidative electropolymerization to improve the Li/S battery performance, as reported in our previous paper. In such a system, the PPy film was coated directly on the S/Ketjenblack cathode to solve the problem of polysulfide dissolution. The optimum PPy film preparation conditions to prevent polysulfide dissolution and to promote Li + permeability were determined by v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
(66 reference statements)
0
26
0
Order By: Relevance
“…Figure c and d presents discharge and charge curves of sulfur and S‐PPy after different cycles, in which the current density and potential range were set at 200 mA g −1 and 1.5–3.0 V, respectively. Both sulfur and S‐PPy shown in Figure c and d exhibit two typical discharge plateaus at about 2.0 and 2.3 V, which are ascribed to the multiple reaction mechanism of elemental sulfur and lithium metal, as described elsewhere, and the inferences are consistent with the CV measurements. The upper and the lower plateaus correspond to changes from cyclic S 8 to higher‐order lithium polysulfides (Li 2 S n , 4< n <8) and to lower‐order polysulfides ( n <4), down to Li 2 S 2 or Li 2 S, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure c and d presents discharge and charge curves of sulfur and S‐PPy after different cycles, in which the current density and potential range were set at 200 mA g −1 and 1.5–3.0 V, respectively. Both sulfur and S‐PPy shown in Figure c and d exhibit two typical discharge plateaus at about 2.0 and 2.3 V, which are ascribed to the multiple reaction mechanism of elemental sulfur and lithium metal, as described elsewhere, and the inferences are consistent with the CV measurements. The upper and the lower plateaus correspond to changes from cyclic S 8 to higher‐order lithium polysulfides (Li 2 S n , 4< n <8) and to lower‐order polysulfides ( n <4), down to Li 2 S 2 or Li 2 S, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Charge/discharge profiles and cycling performance of the halfcell coin cell are presented in Figures 3A,B, respectively. The initial discharge capacity of the cell at 0.2 C was about 1700 mAh g −1 , which after an intrinsic initial irreversible capacity drop stabilized around 1,300 mAh g −1 for 100 cycles (Hara et al, 2015;Nakamura et al, 2016;Wang et al, 2018). The low potential discharge plateau at the first cycle (ΔV ∼ −0.35 V) and large initial discharge capacity is typical behavior for sulfurized polyacrylonitrile composite materials (Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 86%
“…Several sulfur/conductive polymer/conductive carbon ternary composites have been developed and offer an inexpensive alternative, yet their properties can be further optimized (Liang et al, 2016). For instance, polypyrrole-coated sulfur/ ketjen black (S/KB) with 1,047 mAh g −1 initial discharge capacity decays in the performance during cycling due to the dissolution of polysulfides (Nakamura et al, 2016). The composites of sulfur with conductive polymer-polyacrylonitrile have been intensely investigated because it exhibited a capability to accommodate the sulfur volume change upon cycling, prevent polysulfide dissolution, and act as conductivity enhancer (Wang et al, 2002;Peng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The use of conductive polymers as an interlayer has also received attention with examples of electrically conductive polymers such of PANI, PPy, and PEDOT recently demonstrated in addition to ionically conductive Nafion based coatings . Kim et al reported on the utilization of Nafion coated cathodes with a particular emphasis on the importance of complete cathode coverage for maximizing improved electrochemical performance .…”
Section: Cathodementioning
confidence: 99%